Associations between plasma nucleoside reverse transcriptase inhibitors concentrations and cognitive function in people with HIV. - Davide De Francesco; Xinzhu Wang; Laura Dickinson; Jonathan Underwood; Emmanouil Bagkeris; Daphne S Babalis; Patrick W G Mallon; Frank A Post; Jaime H Vera; Memory Sachikonye; Ian Williams; Saye Khoo; et al. (PLoS ONE)
Objectives To investigate the associations of plasma lamivudine (3TC), abacavir (ABC), emtricitabine (FTC) and tenofovir (TFV) concentrations with cognitive function in a cohort of treated people with HIV (PWH). Methods Pharmacokinetics (PK) and cognitive function (Cogstate, six domains) data were obtained from PWH recruited in the POPPY study on either 3TC/ABC or FTC/tenofovir disoproxil fumarate (TDF)-containing regimens. Association between PK parameters (AUC0-24: area under the concentration-time curve over 24 hours, Cmax: maximum concentration and Ctrough: trough concentration) and cognitive scores (standardized into z-scores) were evaluated using rank regression adjusting for potential confounders. Results Median (IQR) global cognitive z-scores in the 83 PWH on 3TC/ABC and 471 PWH on FTC/TDF were 0.14 (-0.27, 0.38) and 0.09 (-0.28, 0.42), respectively. Higher 3TC AUC0-24 and Ctrough were associated with better global z-scores [rho = 0.29 (p = 0.02) and 0.27 (p = 0.04), respectively], whereas higher 3TC Cmax was associated with poorer z-scores [rho = -0.31 (p<0.01)], independently of ABC concentrations. Associations of ABC PK parameters with global and domain z-scores were non-significant after adjustment for confounders and 3TC concentrations (all p's>0.05). None of the FTC and TFV PK parameters were associated with global or domain cognitive scores. Conclusions Whilst we found no evidence of either detrimental or beneficial effects of ABC, FTC and TFV plasma exposure on cognitive function of PWH, higher plasma 3TC exposures were generally associated with better cognitive performance although higher peak concentrations were associated with poorer performance.